Pengaruh Kualitas Pembangunan Manusia terhadap Pertumbuhan Ekonomi Negara-negara ASEAN Tahun 2002-2022 - Pauline Ruth Monica (PT. Hasba Edukasi Mandiri, 2025)
Quality human development is one of the important foundations in driving economic growth, especially in the ASEAN region, which has a heterogeneous level of development. This study aims to analyze the effect of the Human Development Index (HDI), inflation, unemployment rate, and Foreign Direct Investment (FDI) on economic growth in five ASEAN countries, namely Indonesia, Malaysia, Singapore, Thailand, and the Philippines during the period 2002–2022. Secondary data were obtained from the World Bank and UNDP, then analyzed using panel data regression with the Fixed Effect Model (FEM) approach and Driscoll–Kraay standard error to overcome heteroscedasticity and autocorrelation. The results show that HDI has a large positive coefficient (107,387.10) but is not statistically significant, so its contribution to economic growth has not been strongly proven. The inflation variable has a positive and significant effect on the initial model (coefficient of 816.58), although its significance weakens after taking into account country categories. FDI yields inconsistent results, where in some models it has a positive effect, but in other models it is negative and significant (coefficient of –0.004 at the 5% level), so its impact is highly dependent on the structural conditions of each country. Meanwhile, the unemployment rate has a negative coefficient (–768.21) as predicted by theory, but is not significant in all models. These findings indicate that human development is an important prerequisite for long-term economic growth, but in the context of ASEAN, its empirical effect is still weak and influenced by other macroeconomic factors. The policy implications of this study are the importance of strengthening the quality of human development evenly, keeping inflation within moderate limits, and improving infrastructure and institutional capacity so that the benefits of FDI and human capital can be optimally converted into economic growth.